Managing human resources : the new normal - Potgieter, Ingrid Lorraine; Ferreira, Nadia (Switzerland : Springer, 2022)
This book volume crafts an exciting, original account on the changes and requirements on managing human resources within the context of the new normal. Chapters in this book report on current research on the key constructs and processes underlying the management of human resources, both on an organisational strategic level as well as an individual employee level. Chapters compare current research trends in terms of future potential directions for the management of human resources within the context of the new normal. The book also critically evaluates the relevance, applicability and utility of the research findings and theoretical premises in various classical, current and potential emerging issues for research and practice in the smart digital technological world of work for human resource management.
Includes bibliographical references and index.
Keywords: Personnel management